Wet-process ceramic nanofiber thermal insulation material and preparation method thereof
By using modified glass fiber and modified titanium dioxide in ceramic nanofiber insulation materials, combined with wet process and chemical vapor deposition technology, the problems of insufficient flexibility and poor dispersion of existing materials are solved, and high strength, high flexibility and high heat insulation ceramic nanofiber insulation materials are achieved.
Patent Information
- Application Number
- CN202411739127.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-29
- Publication Date
- 2025-03-07
AI Technical Summary
The existing ceramic nanofiber insulation materials have problems of insufficient flexibility and poor dispersion, which leads to the insulating performance being unable to be well improved.
Ceramic nanofibers are used as the main material, modified glass fibers and inorganic functional fillers are used as auxiliary materials, and glass fibers and titanium dioxide are modified through chemical vapor deposition and oxidation-self-polymerization methods, dispersants and adhesives are added, and thermal insulation materials are synthesized using a wet process.
The high strength, high flexibility and high thermal insulation of ceramic nanofiber insulation materials are achieved, the problems of insufficient flexibility and poor dispersion are solved, and the overall performance of the material is improved.
Smart Images

Figure BDA0005162211980000071 
Figure BDA0005162211980000081
Abstract
Description
Technical Field
[0001] The invention relates to the field of thermal insulation materials, and in particular to a wet-process ceramic nanofiber thermal insulation material and a preparation method thereof. Background Art
[0002] With the rapid development of China's economy, energy conservation, that is, reducing heat loss, improving the utilization efficiency of thermal energy, and reducing energy waste, has become an important way to solve energy shortages and relatively backward energy development. One of the most important measures for energy conservation is the development and application of thermal insulation materials. The use of thermal insulation materials can effectively reduce heat loss and save fuel. At the same time, it can improve the working environment, ensure safe production, and improve work efficiency. It has important practical significance for the healthy and stable development of my country's economic construction.
[0003] Ceramic nanofibers have many advantages such as high temperature resistance, oxidation resistance, good thermal stability and good mechanical vibration resistance, so they can be used as the main component of thermal insulation materials alone. They have broad application prospects in the fields of heat insulation, thermal insulation, sound absorption and noise reduction.
[0004] However, there are still some unresolved problems with the ceramic nanofiber thermal insulation materials currently on the market. For example, in order to enhance the strength of ceramic nanofiber thermal insulation materials, some high-strength materials such as glass fibers are often added, but there may be a problem of insufficient flexibility; and in order to further improve the overall thermal insulation performance of the material, some filler components with high thermal insulation and light-shielding properties may be added, such as silica, titanium dioxide, etc., but these materials may also have problems of easy agglomeration and poor dispersion, which makes it impossible to improve the thermal insulation performance of the material.
[0005] Patent CN 111848105A discloses a composite thermal insulation material containing ceramic fibers and a preparation method thereof. The composite thermal insulation material includes raw materials such as ceramic fiber wool, hollow glass microspheres, nano-titanium dioxide, inorganic binders, organic binders and dispersants, so that the ceramic fiber thermal insulation material has high strength and good thermal insulation performance. However, the nano-titanium dioxide used in this application generally has the problem of poor dispersibility, which may cause the strength and thermal insulation performance of the ceramic fiber thermal insulation material to decrease.
[0006] Therefore, there is an urgent need on the market for a wet-process ceramic nanofiber thermal insulation material with high strength, high flexibility and high thermal insulation. Summary of the invention
[0007] In response to the problems existing in the prior art, the present invention uses ceramic nanofibers as the main material, modified glass fibers and inorganic functional fillers as auxiliary materials, dispersants and adhesives as auxiliary agents, and adds them into deionized water to synthesize a wet-process ceramic nanofiber thermal insulation material, which has the advantages of high strength, high flexibility and high thermal insulation.
[0008] In order to achieve the above object, the technical solution adopted by the present invention is as follows:
[0009] On the one hand, the present invention provides a wet-process ceramic nanofiber thermal insulation material, which comprises the following raw materials, by weight: 50-70 parts of ceramic nanofibers, 15-25 parts of modified glass fibers, 5-15 parts of inorganic functional fillers, 4-10 parts of dispersants, 2-6 parts of adhesives, and 200-300 parts of deionized water.
[0010] In some embodiments of the present invention, the ceramic nanofiber is any one of SiO2 nanofiber, Al2O3 nanofiber, and SiO2 / Al2O3 composite nanofiber, by weight.
[0011] In some embodiments of the present invention, the method for preparing the modified glass fiber comprises the following steps:
[0012] (1) placing the glass fiber at 1-1.5 Pa for 15-30 min, heating it to 1000-1100° C., introducing ethanol vapor, argon and hydrogen, reacting for 60-70 min, and cooling it to room temperature to obtain product 1 for later use;
[0013] (2) heating the borane ammonia complex to 80-90° C. to obtain a pretreated borane ammonia complex for standby use, allowing the product 1 of step (1) to stand at 1-1.5 Pa for 15-30 min, heating to 1000-1100° C., adding the pretreated borane ammonia complex, introducing argon and hydrogen, reacting for 1-3 h, and cooling to room temperature to obtain a product 2 for standby use;
[0014] (3) Add the product 2 of step (2) into a Tris-HCl buffer solution, stir while ultrasonicating, add dopamine hydrochloride, shake, filter, wash, and dry to obtain a modified glass fiber.
[0015] In some embodiments of the present invention, in step (2), the mass ratio of product 1 to borane ammonia complex is 1:(0.5-0.7).
[0016] Preferably, in step (2), the mass ratio of product 1 to borane ammonia complex is 1:0.6.
[0017] In some embodiments of the present invention, in step (3), the mass ratio of product 2 to dopamine hydrochloride is 1:(0.06-0.1).
[0018] Preferably, in step (3), the mass ratio of product 2 to dopamine hydrochloride is 1:0.08.
[0019] Glass fiber has good heat resistance and strength. Adding it to ceramic nanofiber insulation materials can enhance mechanical properties, heat resistance and thermal insulation, playing a vital role. However, the glass fiber itself has a large rigidity, resulting in its lack of flexibility, which limits its application in the field of flexible materials.
[0020] On the one hand, the applicant uses glass fiber as a matrix and adopts a chemical vapor deposition method to grow graphene on the surface of the glass fiber. The single atomic layer structure of graphene gives it good flexibility, thereby greatly improving the flexibility of the glass fiber. Furthermore, the applicant continues to grow boron nitride on the surface of graphene, which improves the thermal stability, chemical stability and mechanical strength of the graphene-modified glass fiber. On the other hand, the applicant uses an oxidation-self-polymerization method to coat dopamine on the surface of the above-mentioned boron nitride and graphene-modified glass fiber to synthesize modified glass fiber, so that the modified glass fiber has higher dispersibility and stability.
[0021] In some embodiments of the present invention, the inorganic functional filler is a mixture of hollow glass microspheres and modified titanium dioxide.
[0022] Preferably, the mass ratio of the hollow glass microspheres to the modified titanium dioxide is (2-3):1.
[0023] In some embodiments of the present invention, the method for preparing the modified titanium dioxide comprises the following steps:
[0024] 1) Mix 11-cyanoundecyltrichlorosilane and acetic anhydride, heat to 60-80° C., stir for 5-7 hours, and distill under reduced pressure to obtain a product for later use;
[0025] 2) Mix the product of step 1) with deionized water, heat to 60-70° C., stir for 2-3 hours, add titanium dioxide, heat to 80-90° C., soak, filter, wash, and dry to obtain modified titanium dioxide.
[0026] In some embodiments of the present invention, in step 2), the mass ratio of the product to titanium dioxide is 1:(2.5-3.5).
[0027] Preferably, in step 2), the mass ratio of the product to titanium dioxide is 1:3.
[0028] Titanium dioxide has good thermal insulation properties due to its high reflection and low absorption of sunlight, and is often added to thermal insulation materials as a thermal insulation filler. It can also improve the overall strength of the material to a certain extent. However, titanium dioxide material itself is easy to agglomerate, resulting in poor dispersion.
[0029] The applicant uses 11-cyanoundecyltrichlorosilane and excess acetic anhydride to synthesize a new type of silane coupling agent (product) containing cyano group, and uses the product to modify titanium dioxide. The product reacts with the hydroxyl groups on the surface of titanium dioxide to effectively improve the dispersibility of titanium dioxide. In addition, because the product has a long-chain alkyl structure, its steric hindrance is relatively large, which further increases its dispersing effect on titanium dioxide.
[0030] Furthermore, the cyano group in the modified titanium dioxide structure may undergo certain hydrogen bonding with the phosphate and sulfonate structures in the dispersant, thereby improving the overall stability of the ceramic nanofiber thermal insulation material.
[0031] In some embodiments of the present invention, the dispersant is any one of sodium hexametaphosphate, sodium dodecyl sulfonate, and sodium dodecylbenzene sulfonate.
[0032] In some embodiments of the present invention, the adhesive is aluminum sol or starch.
[0033] Another aspect of the present invention further provides a method for preparing the wet-process ceramic nanofiber thermal insulation material described in the above technical solution, comprising the following steps:
[0034] The ceramic nanofiber, modified glass fiber, inorganic functional filler, dispersant and adhesive are added into deionized water, stirred, filtered, molded and dried to obtain a wet-process ceramic nanofiber thermal insulation material.
[0035] Compared with the prior art, the present invention has the following beneficial effects:
[0036] (1) The present invention uses ceramic nanofibers as the main material, modified glass fibers and inorganic functional fillers as auxiliary materials, and dispersants and adhesives as auxiliary agents, and adds them into deionized water to synthesize a wet-process ceramic nanofiber thermal insulation material. Through the synergistic effect of the various components, the wet-process ceramic nanofiber thermal insulation material has the advantages of high strength, high flexibility and high thermal insulation.
[0037] (2) The present invention uses glass fiber as a matrix, adopts a chemical vapor deposition method to grow graphene on the surface of the glass fiber, and then uses dopamine to coat and modify the synthesized modified glass fiber, so that the flexibility, strength and dispersibility of the glass fiber are improved, thereby improving the flexibility, strength and thermal insulation performance of the thermal insulation material.
[0038] (3) The present invention uses 11-cyanoundecyltrichlorosilane and excess acetic anhydride to synthesize a new type of silane coupling agent containing cyano group to modify titanium dioxide, so that the modified titanium dioxide has high dispersibility, thereby improving the thermal insulation performance and strength of the thermal insulation material.
[0039] (4) The wet-process ceramic nanofiber thermal insulation material prepared by the present invention has high strength, high flexibility and high thermal insulation, can be widely used in the field of thermal insulation materials, and has good commercial application value. DETAILED DESCRIPTION
[0040] The present invention will be described below in conjunction with specific embodiments. It should be noted that the following embodiments are examples of the present invention and are only used to illustrate the present invention, but not to limit the present invention. Other combinations and various modifications within the concept of the present invention may be performed without departing from the spirit or scope of the present invention.
[0041] In the following embodiments and comparative examples, except for modified glass fiber and modified titanium dioxide, the other compound monomers and related reagents used can be purchased from the market. Among them, SiO2 nanofibers, Al2O3 nanofibers and SiO2 / Al2O3 composite nanofibers are all existing products of the company; glass fiber was purchased from Lingshou County Jiashuo Building Materials Processing Co., Ltd.; hollow glass microspheres with an average particle size of 30 μm were purchased from Shijiazhuang Donghao Chemical Research Institute Co., Ltd.; starch was purchased from Suzhou Anxin Fine Chemical Co., Ltd.
[0042] Preparation Example 1
[0043] The synthetic method of modified glass fiber A comprises the following steps:
[0044] (1) 6 g of glass fiber was placed at 1.2 Pa for 20 min, heated to 1050° C., introduced with 200 sccm of ethanol vapor, 100 sccm of argon, and 100 sccm of hydrogen, reacted for 65 min, and cooled to room temperature to obtain product 1 for later use;
[0045] (2) 3 g of borane ammonia complex was heated to 85° C. to obtain a pretreated borane ammonia complex for use, 5 g of the product 1 of step (1) was allowed to stand at 1.2 Pa for 20 min, the temperature was raised to 1050° C., the pretreated borane ammonia complex, 100 sccm of argon and 100 sccm of hydrogen were added, the reaction was continued for 2 h, and the product 2 was obtained after cooling to room temperature;
[0046] (3) 5 g of the product 2 of step (2) was added to 200 ml of a pH = 9 Tris-HCl buffer solution, and the mixture was stirred for 1 h while ultrasonicating. 0.4 g of dopamine hydrochloride was added, and the mixture was shaken for 24 h. The mixture was filtered, washed with deionized water for 3 times, and vacuum dried at 95 ° C for 12 h to obtain a modified glass fiber A.
[0047] Preparation Example 2
[0048] The specific implementation manner of modified glass fiber B is the same as that of modified glass fiber A, except that in step (2), the mass of borane ammonia complex is replaced with 1.5 g.
[0049] Preparation Example 3
[0050] The specific implementation manner of modified glass fiber C is the same as that of modified glass fiber A, except that in step (3), the mass ratio of dopamine hydrochloride is 0.2 g.
[0051] Preparation Example 4
[0052] The synthesis method of modified titanium dioxide A comprises the following steps:
[0053] 1) Mix 10 g of 11-cyanoundecyltrichlorosilane and 40 g of acetic anhydride, heat to 70° C., stir for 6 h, and distill under reduced pressure to obtain a product for later use;
[0054] 2) Mix 5 g of the product of step 1) with 500 ml of deionized water, heat to 65° C., stir for 2.5 h, add 15 g of titanium dioxide, heat to 85° C., soak for 3 h, filter, wash with anhydrous ethanol 3 times, and dry at 80° C. for 12 h to obtain modified titanium dioxide A.
[0055] Preparation Example 5
[0056] The specific implementation manner of modified titanium dioxide B is the same as that of modified titanium dioxide A, except that in step 2), the mass of the product is replaced with 3.7 g.
[0057] Example 1
[0058] A wet-process ceramic nanofiber thermal insulation material comprises the following raw materials by weight: 60 parts of SiO2 / Al2O3 composite nanofibers, 20 parts of modified glass fiber A, 10 parts of inorganic functional filler, 7 parts of sodium hexametaphosphate, 4 parts of starch and 250 parts of deionized water.
[0059] The inorganic functional filler includes hollow glass microspheres and modified titanium dioxide A in a mass ratio of 2.5:1.
[0060] The preparation method of the wet-process ceramic nanofiber thermal insulation material in this embodiment comprises the following steps:
[0061] SiO2 / Al2O3 composite nanofibers, modified glass fiber A, inorganic functional filler, sodium hexametaphosphate and starch were added to deionized water, stirred for 2 hours, filtered, molded, and dried at 105°C for 12 hours to obtain wet-process ceramic nanofiber thermal insulation material. The filtration mesh aperture was 200um and the molding pressure was 3MPa.
[0062] Example 2
[0063] A wet-process ceramic nanofiber thermal insulation material comprises the following raw materials by weight: 50 parts of SiO2 nanofiber, 20 parts of modified glass fiber A, 5 parts of inorganic functional filler, 4 parts of sodium dodecyl sulfate, 2 parts of aluminum sol and 200 parts of deionized water.
[0064] The inorganic functional filler includes hollow glass microspheres and modified titanium dioxide A in a mass ratio of 2:1.
[0065] The preparation method of the wet-process ceramic nanofiber thermal insulation material in this embodiment comprises the following steps:
[0066] SiO2 nanofibers, modified glass fiber A, inorganic functional fillers, sodium dodecyl sulfate and aluminum sol were added to deionized water, stirred for 2 hours, filtered, molded, and dried at 105°C for 12 hours to obtain wet-process ceramic nanofiber insulation materials. The filtration mesh aperture was 200um and the molding pressure was 3MPa.
[0067] Example 3
[0068] A wet-process ceramic nanofiber thermal insulation material comprises the following raw materials by weight: 70 parts of Al2O3 nanofiber, 20 parts of modified glass fiber A, 15 parts of inorganic functional filler, 10 parts of sodium dodecylbenzene sulfonate, 6 parts of starch and 300 parts of deionized water.
[0069] The inorganic functional filler includes hollow glass microspheres and modified titanium dioxide A in a mass ratio of 3:1.
[0070] The preparation method of the wet-process ceramic nanofiber thermal insulation material in this embodiment comprises the following steps:
[0071] Al2O3 nanofibers, modified glass fiber A, inorganic functional filler, sodium dodecylbenzene sulfonate and starch were added to deionized water, stirred for 2 hours, filtered, molded, and dried at 105°C for 12 hours to obtain wet-process ceramic nanofiber insulation material. The filtration mesh aperture was 200um and the molding pressure was 3MPa.
[0072] Example 4
[0073] A wet-process ceramic nanofiber thermal insulation material comprises the following raw materials by weight: 55 parts of SiO2 / Al2O3 composite nanofibers, 15 parts of modified glass fiber A, 10 parts of inorganic functional filler, 5 parts of sodium hexametaphosphate, 3 parts of starch, and 230 parts of deionized water.
[0074] The inorganic functional filler includes hollow glass microspheres and modified titanium dioxide A in a mass ratio of 2.5:1.
[0075] The preparation method of the wet-process ceramic nanofiber thermal insulation material in this embodiment is the same as that in Example 1.
[0076] Example 5
[0077] A wet-process ceramic nanofiber thermal insulation material comprises the following raw materials by weight: 65 parts of SiO2 / Al2O3 composite nanofibers, 25 parts of modified glass fiber A, 10 parts of inorganic functional filler, 9 parts of sodium hexametaphosphate, 5 parts of starch and 270 parts of deionized water.
[0078] The inorganic functional filler includes hollow glass microspheres and modified titanium dioxide A in a mass ratio of 2.5:1.
[0079] The preparation method of the wet-process ceramic nanofiber thermal insulation material in this embodiment is the same as that in Example 1.
[0080] Example 6
[0081] This embodiment provides a wet-process ceramic nanofiber thermal insulation material and a preparation method thereof. The specific implementation method is the same as that of Example 1, except that the modified glass fiber A is replaced by the modified glass fiber B in equal amounts.
[0082] Example 7
[0083] This embodiment provides a wet-process ceramic nanofiber thermal insulation material and a preparation method thereof. The specific implementation method is the same as that of Example 1, except that the modified glass fiber A is replaced by the modified glass fiber C in equal amounts.
[0084] Example 8
[0085] This embodiment provides a wet-process ceramic nanofiber thermal insulation material and a preparation method thereof. The specific implementation method is the same as that of Example 1, except that modified titanium dioxide B replaces modified titanium dioxide A in equal amounts.
[0086] Comparative Example 1
[0087] This comparative example provides a wet-process ceramic nanofiber thermal insulation material and a preparation method thereof. The specific implementation method is the same as that of Example 1, except that an equal amount of glass fiber is used to replace the modified glass fiber A.
[0088] Comparative Example 2
[0089] This embodiment provides a wet-process ceramic nanofiber thermal insulation material and a preparation method thereof. The specific implementation method is the same as that of Example 1, except that an equal amount of titanium dioxide is used to replace modified titanium dioxide A.
[0090] Performance Testing
[0091] The strength, flexibility and thermal insulation performance of the wet-process ceramic nanofiber thermal insulation materials of the above Examples 1-8 and Comparative Examples 1-2 were tested, and the test results are shown in Table 1.
[0092] (1) Strength
[0093] The strength is determined by testing the compressive strength, with reference to standard GB / T 5072-2008.
[0094] (2) Flexibility
[0095] Flexibility is determined by testing the rebound performance, referring to the standard BS1902-6-1986.
[0096] (3) Thermal insulation performance
[0097] The thermal insulation performance is judged by testing the room temperature thermal conductivity, with reference to the standard YB / T 4130-2005.
[0098] Table 1
[0099]
[0100]
[0101] It can be seen from the data in Table 1 that the wet-process ceramic nanofiber thermal insulation materials in Examples 1-5 of the present invention have good strength, flexibility and thermal insulation as a whole. Among them, Examples 6-7 changed the addition ratio of the main components in the synthesis process of the modified glass fiber, so that the flexibility, stability, mechanical strength and thermal insulation of the modified glass fiber were not well improved, resulting in a decrease in the strength, flexibility and thermal insulation of the thermal insulation material; Example 8 changed the modification ratio of the synthesized new silane coupling agent to titanium dioxide, so that the dispersibility of the modified titanium dioxide was not well improved, which led to a decrease in the strength, flexibility and thermal insulation of the wet-process ceramic nanofiber thermal insulation material; Comparative Examples 1-2 respectively selected glass fiber and titanium dioxide to replace the modified glass fiber A and modified titanium dioxide A in equal amounts, and the test found that the strength, flexibility and thermal insulation of the wet-process ceramic nanofiber thermal insulation material showed poor results.
[0102] The above implementation modes are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with this technology to understand the content of the present invention and implement it, and they cannot be used to limit the protection scope of the present invention. Any equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.
Claims
1. A wet-process ceramic nanofiber thermal insulation material, characterized in that: The wet-process ceramic nanofiber thermal insulation material comprises the following raw materials by weight: 50-70 parts of ceramic nanofibers, 15-25 parts of modified glass fibers, 5-15 parts of inorganic functional fillers, 4-10 parts of dispersants, 2-6 parts of adhesives, and 200-300 parts of deionized water.
2. The wet-process ceramic nanofiber thermal insulation material according to claim 1, characterized in that: The ceramic nanofiber is any one of SiO2 nanofiber, Al2O3 nanofiber and SiO2 / Al2O3 composite nanofiber.
3. The wet-process ceramic nanofiber thermal insulation material according to claim 1, characterized in that: The preparation method of the modified glass fiber comprises the following steps: (1) placing the glass fiber at 1-1.5 Pa for 15-30 min, heating it to 1000-1100° C., introducing ethanol vapor, argon and hydrogen, reacting for 60-70 min, and cooling it to room temperature to obtain product 1 for later use; (2) heating the borane ammonia complex to 80-90° C. to obtain a pretreated borane ammonia complex for standby use, allowing the product 1 of step (1) to stand at 1-1.5 Pa for 15-30 min, heating to 1000-1100° C., adding the pretreated borane ammonia complex, introducing argon and hydrogen, reacting for 1-3 h, and cooling to room temperature to obtain a product 2 for standby use; (3) adding the product 2 of step (2) into a Tris-HCl buffer solution, stirring while ultrasonicating, adding dopamine hydrochloride, shaking, filtering, washing, and drying to obtain a modified glass fiber.
4. The wet-process ceramic nanofiber thermal insulation material according to claim 3, characterized in that: In the step (2), the mass ratio of the product 1 to the borane ammonia complex is 1:(0.5-0.7).
5. The wet-process ceramic nanofiber thermal insulation material according to claim 3, characterized in that: In the step (3), the mass ratio of the product 2 to dopamine hydrochloride is 1:(0.06-0.1).
6. The method for preparing a wet-process ceramic nanofiber thermal insulation material according to claim 1, characterized in that: The inorganic functional filler is a mixture of hollow glass microspheres and modified titanium dioxide.
7. The wet-process ceramic nanofiber thermal insulation material according to claim 6, characterized in that: The preparation method of the modified titanium dioxide comprises the following steps: 1) Mix 11-cyanoundecyltrichlorosilane and acetic anhydride, heat to 60-80° C., stir for 5-7 hours, and distill under reduced pressure to obtain a product for later use; 2) Mix the product of step 1) with deionized water, heat to 60-70° C., stir for 2-3 hours, add titanium dioxide, heat to 80-90° C., soak, filter, wash, and dry to obtain modified titanium dioxide.
8. The wet-process ceramic nanofiber thermal insulation material according to claim 6, characterized in that: In the step 2), the mass ratio of the product to titanium dioxide is 1:(2.5-3.5).
9. The method for preparing a wet-process ceramic nanofiber thermal insulation material according to claim 1, characterized in that: The dispersant is any one of sodium hexametaphosphate, sodium dodecyl sulfonate and sodium dodecylbenzene sulfonate.
10. A method for preparing a wet-process ceramic nanofiber thermal insulation material according to any one of claims 1 to 9, characterized in that: The following steps are involved: The ceramic nanofiber, modified glass fiber, inorganic functional filler, dispersant and adhesive are added into deionized water, stirred, filtered, molded and dried to obtain a wet-process ceramic nanofiber thermal insulation material.
Citation Information
Patent Citations
Composite thermal insulation material containing ceramic fiber and preparation method thereof
CN111848105A
Cited By
Inorganic fiber insulation board based on dry method and preparation method thereof
CN121159223A
Fiber-reinforced light fireproof thermal insulation board and preparation method thereof
CN122358547A
Fiber-reinforced lightweight fireproof thermal insulation board and preparation method thereof
CN122358547B